Is there a role for the adverse outcome pathway framework to support radiation protection?. (1st February 2019) - Chauhan, Vinita; Said, Zakaria; Daka, Joseph; Sadi, Baki; Bijlani, Deepti; Marchetti, Francesco; Beaton, Danielle; Gaw, Adelene; Li, Chunsheng; Burtt, Julie; Leblanc, Julie; Desrosiers, Marc; et al.
Abstract: Purpose: In 2012, the Organization for Economic Cooperation and Development (OECD) formally launched the Adverse Outcome Pathway (AOP) Programme. The AOP framework has the potential for predictive utility in identifying early biological endpoints linked to adverse effects. It uses the weight of correlative evidence to identify a minimal set of measurable key events that link molecular initiating events to an adverse outcome. AOPs have the capability to identify knowledge gaps and priority areas for future research based on relevance to an adverse outcome. In addition, AOPs can identify pathways that are common among multiple stressors, thereby allowing for the possibility of refined risk assessments based on co-exposure considerations. The AOP framework is increasingly being used in chemical and ecological risk assessment; however, its use in the development of radiation-specific pathways has yet to be fully explored. To bring awareness of the AOP framework to the Canadian radiation community, a workshop was held in Canada in June 2018 that brought together radiation experts from Health Canada, the Canadian Nuclear Laboratories, and the Canadian Nuclear Safety Commission. Methods: The purpose of the workshop was to share knowledge on the AOP framework, specifically (1) to introduce the concept of the AOP framework and its possible utility to Canadian radiation experts; (2) to provide examples on how it has advanced risk assessment; (3) to discuss an illustrative example specific to ionizing radiation; and lastly (4) to identify the broad benefits and challenges of the AOP framework to the radiation community. Results: The participants showed interest in the framework, case examples were described and areas of challenge were identified. Herein, we summarize the outcomes of the workshop. Conclusions: Overall, participants agreed that by building AOPs in the radiation field, a network of data-sharing initiatives will enhance our interpretation of existing knowledge where current scientific evidence is minimal. They would provide new avenues to understand effects at low-dose and dose-rates and help to quantify the combined effect of multiple stressors on shared mechanistic pathways.